2020
DOI: 10.1038/s41598-020-58458-w
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: A Complete Formula of Ocean Surface Absolute Geostrophic Current

Abstract: A complete formula of ocean Surface Absolute Geostrophic current peter c. chu Absolute geostrophic current at the ocean surface (S) contains three components: (1) absolute geostrophic current at the geoid undulation (N), (2) geostrophic shear (between S and N) due to horizontal gradient of dynamic ocean topography, and (3) geostrophic shear (between S and N) due to horizontal gradient of density. However, only the second component is used to represent the surface absolute geostrophic current in physical oceano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(4) and (5) the potential of the real gravity is given by From Eq. (6) the real gravity is represented by The horizontal gravity component at the reference ellipsoid surface (z = 0) is obtained using (7) and (10) 12,13 An approximate 3D gravity field for oceanography. According to Eq.…”
Section: Openmentioning
confidence: 99%
“…(4) and (5) the potential of the real gravity is given by From Eq. (6) the real gravity is represented by The horizontal gravity component at the reference ellipsoid surface (z = 0) is obtained using (7) and (10) 12,13 An approximate 3D gravity field for oceanography. According to Eq.…”
Section: Openmentioning
confidence: 99%
“…These results suggested that volume transport estimated from altimeter measurements should be taken with care when considering the EAuC extending to the bottom 12,15 . Whilst geostrophic velocity estimates have their limitations 17 , they adequately represented long term variability of the upper-half water column on the continental slope (M4) and rise (M5), answering Wunsch's (1997) 18 main question: "given the surface geostrophic velocity as measured by an altimeter, how is the motion to be interpreted as a function of depth?" for the studied region.…”
Section: Discussionmentioning
confidence: 99%